A feast of learning : international perspectives on adult learning and change - Hiemstra, Roger; Carré, Philippe (Adult education special topics., 2013)
This book provides perspectives from authors in six countries (Canada, Colombia, Germany, France, UK, USA) pertaining to adult learning in the 21st Century. This book grew out of an exciting International Conference on Adult Learning (ICAL) held in Paris, May 27-29, 2012. Imagine "listening in" as these international scholars, representing expertise in various areas related to adult education, focus their collective attention to the topic of adult learning. Their task is to concentrate their research and intellectual acumen on where adult learning is heading in the 21st Century and to bring together their varied areas of expertise to expand the field of adult education's knowledge base. This book provides more than a record of their papers and meetings. Instead, each author has revised their paper with symposium feedback to help capture the discussion, synergy and growing knowledge base we envision together. Now you can read how these leading scholars understand adult learning in light on their collective work. Areas of focus include * Heuristics of Adult Learning * Facilitating Self Directed Learning * Individuals and the Learning Process * Executives' Self-Development * Distance Learning * Science Self Directed Learning for All * Entertainment-Education Communication Strategy * Positive Deviance to Transform Education * Learning Through the Life Course This book will benefit teachers, researchers, administrators, and students in the field of adult education, learning, and practice. The synergistic result of bringing together nine scholars results in many new practical applications, research streams, scholarship, and practice suggestions.